Do we prescribe what patients prefer?: pilot study to assess patient preferences for medication regimen characteristics - Witticke, Diana; Seidling, Hanna; Klimm, Hans-Dieter; Haefeli, Walter E. (Patient preference and adherence, 2012)
Do we prescribe what patients prefer? Pilot study to assess patient preferences for medication regimen characteristics Diana Witticke,1,2 Hanna Marita Seidling,1,2 Hans-Dieter Klimm,3 Walter Emil Haefeli1,21Department of Clinical Pharmacology and Pharmacoepidemiology, 2Cooperation Unit Clinical Pharmacy, 3Department of General Practice and Health Service Research, University of Heidelberg, Heidelberg, GermanyBackground: The aim of this pilot study was to evaluate patients' self-reported attitudes towards medication-related factors known to impair adherence and to assess their prevalence in ambulatory care as an essential prerequisite to improve patient adherence.Methods: We conducted a face-to-face interview with 110 primary care patients maintained on at least one drug. For each drug, the patient was asked to specify medication-related factors of interest, ie, dosage form, dosage interval, required relationship with food intake, and the planned time of day for intake, and to rate the individual relevance of each prevalent parameter on a three-point Likert scale (discriminating between prefer, neutral, and dislike).Results: Tablets with a once-daily dosage frequency were the most preferred dosage form, with a high prevalence in the ambulatory setting. Drug intake in the morning and evening were most preferred, and drug intake at noon was least preferred, but also had a low prevalence in contrast with drug intake independent of meals that was most preferred. Interestingly, only one quarter (26.4%) of all the patients were able to indicate clear preferences or dislikes.Conclusion: When patients are asked to specify their preferences for relevant medication regimen characteristics, they clearly indicated regimens that have been associated with better adherence in earlier studies. Therefore, our results suggest that adaptation of drug regimens to individual preferences might be a promising strategy to improve adherence. Because the German health care system may differ from other systems in relevant aspects, our findings should be confirmed by evaluation of patient preferences in other health care systems. Once generalizability of the study results is shown, these findings could be a promising basis upon which to promote patient adherence right from the beginning of drug therapy.Keywords: patient perception, medication regimen complexity, adherence